Development of strawberry flavored peanut beverage - Aquino, Mirasol Bobiles; Azanza, Ma. Patricia V. (1997)
The general objective of the study was to develop an acceptable strawberry-flavored and -colored peanut beverage. The first phase of the study involved the production of the peanut beverage using the modified Illinois Process (Rubico et al., 1989). The most acceptable strawberry flavor and color concentrations to be incorporated into the peanut beverage were determined through sensory evaluations. The strawberry flavor concentrations used were 0.1%, 0.4% and 0.7%. The red color concentrations used were 0.0025%, 0.05% and 0.15% which corresponded to the Munsell colors chosen through incorporation pre-testing. The most acceptable strawberry flavor and color concentrations were 0.7% and 0.05%, respectively. Laboratory scale production of the most acceptable strawberry-flavored and -colored peanut beverage and storage stability study were done in the second phase of the study. The strawberry-flavored and -colored peanut beverage was packaged in high-density polyethylene bottles and stored at refrigerator temperature (5oC) for 9 days. Quality assessment of the raw peanut, unflavored peanut beverage and strawberry flavored peanut beverage were done every three days through microbiological and physico-chemical analysis. Microbiological tests included Total Plate Count, Yeast and Mold Count, and Aspergillus flavus and A. parasiticus Count. Sampling was terminated when physical and chemical degradation of the beverage which would make it unfit for human consumption was observed. The storage study of the strawberry flavored peanut beverage lasted for 9 days. Th Pn 4 peanut cultivar and the unflavored peanut beverage had a total plate count of 7.3 x 102 cfu/gm and <10 cfu/ml, respectively. The TPC of the SFPB increased from 1.36 x 104 to 1.83 x 105 cfu/ml from day 0 to day 9, respectively. The YMC for Pn 4 peanut and unflavored peanut beverage and the SFPB all had an A. flavus and A. parasiticus count of <100 cfu/ml. The pH of the unflavored peanut beverage was 6.73. The pH of the SFPB decreased during storage of 0 to 9 days from 6.19 to 4.97, respectively. The % soluble solids of the unflavored peanut beverage was 10.83. Upon addition of flavor and color, the % SS increased to 11 and remained at this reading during the 9 day test storage. The color of the SFPB did not change throughout the storage period of 9 days at refrigerator temperature (5oC). The third phase involved the cost analysis of the SFPB. The unit cost of the SFPB was estimated to be P5.31 per 250 ml. The recommended selling price of the SFPB, which already includes a 10% mark-up, was estimated to be P5.84 per 250 ml.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Beverages